Documental Teatro Santander - Díaz Ardila, José Antonio; Barrera Ruiz, Sandra; Turbay de Liévano, Edith; Beatriz Gonzales, Maestra; Prada, Miguel Antonio (Universidad Autónoma de Bucaramanga UNAB, 2021)
10:20 minutos